2019
DOI: 10.1039/c9cp04135d
|View full text |Cite
|
Sign up to set email alerts
|

Photoexcited triplet states of twisted acenes investigated by Electron Paramagnetic Resonance

Abstract: Increased twisting of the anthracene core affects the ISC efficiency and induces changes in zero-field splitting parameters, spin polarisation and hyperfine couplings.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…While optical spectroscopy has proved a powerful tool to examine the photophysics and spinconversion rates in TADF 30,31,35,36 , trESR provides a complementary window into the underlying spin physics. TrESR is sensitive to paramagnetic states and can therefore probe the formation dynamics and coupling mechanisms of triplet excitons 37 , as highlighted by broad applications in studying triplet excitons in organic photovoltaics [38][39][40] , singlet fission [41][42][43][44] , photosensitizers 37,[45][46][47] , and molecular electronics 48,49 . Because trESR is not sensitive to singlet excitons (due to their diamagnetism) it can only explicitly probe forward ISC.…”
mentioning
confidence: 99%
“…While optical spectroscopy has proved a powerful tool to examine the photophysics and spinconversion rates in TADF 30,31,35,36 , trESR provides a complementary window into the underlying spin physics. TrESR is sensitive to paramagnetic states and can therefore probe the formation dynamics and coupling mechanisms of triplet excitons 37 , as highlighted by broad applications in studying triplet excitons in organic photovoltaics [38][39][40] , singlet fission [41][42][43][44] , photosensitizers 37,[45][46][47] , and molecular electronics 48,49 . Because trESR is not sensitive to singlet excitons (due to their diamagnetism) it can only explicitly probe forward ISC.…”
mentioning
confidence: 99%
“… 9 , 10 , 18 , 20 We have previously demonstrated that as twisting increases, the rate of ISC to the triplet state also increases. 21 Therefore, it is expected that as the twisting increases, the mechanism that involves ISC will become more dominant. When using MB as the sensitizer, the faster reaction rate with twisting can be explained by the calculated lower energy for the transition state of twisted Ant-C3 compared with less-twisted Ant-C6 , as detailed later.…”
mentioning
confidence: 99%
“…[1e,10] In the twistacene case, the reduction in fluorescence quantum efficiency arose from stabilization of the triplet state with increasing twist. [11] The synthetic challenges for obtaining curved PAHs are exemplified in the field of carbon nanobelts (CNBs). Cyclacene [9a,20] and the "Vögtle belt" [12] are examples of desired molecules that have not yet been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1e , 10 ] In the twistacene case, the reduction in fluorescence quantum efficiency arose from stabilization of the triplet state with increasing twist. [11] …”
Section: Introductionmentioning
confidence: 99%